Integration of Artificial Intelligence (AI) and Internet of Things (IoT) in Smart Agriculture - Bara, Zuraida Julhiji; Riasat, Shahroz; Ahsan Khan , Muhammad (Bincang Sains dan Teknologi, 2025)
The integration of Artificial Intelligence (AI) and the Internet of Things (IoT) is revolutionizing modern agriculture by enabling precision, automation, and data-driven decision-making across various farming domains. This paper explores key applications of AI-IoT systems, including precision resource management, smart irrigation, crop health monitoring, and livestock management. Precision farming techniques supported by AI-IoT models achieve high accuracy (98.65%) and efficiency, significantly improving input optimization through variable rate application and real-time insights. Smart irrigation systems, such as “Vital,” demonstrate the effective use of explainable AI and low-cost sensors to automate water usage based on soil and weather data. Additionally, AI-IoT integration enhances crop protection through early disease detection and improves animal welfare via continuous livestock monitoring. The environmental benefits are notable, with reduced resource waste and lower greenhouse gas emissions, while economic advantages include increased productivity and supply chain efficiency. Despite the potential, challenges remain in infrastructure, cost, and user training. Emerging innovations such as edge computing, digital twins, and cloud-based management systems are shaping the future of smart agriculture, promising more autonomous, sustainable, and accessible solutions for global food security.